FRI0645 Nailfold capillaroscopy in diabetes mellitus type 2. (15th June 2017) - Maldonado, G; Paredes, C; Guerrero, R; Ríos, C
Abstract : Background: Diabetes mellitus (DM) is characterized by chronic hyperglycemia states and the development of specific microvascular disorders such as retinopathy and nephropathy. Conventional methods are usually used to study the vascular compromise of this entity, however, the use of capillaroscopy for the evaluation of capillary microarchitecture is not frequently used. Objectives: The objective of this study was to identify vascular alterations in patients with type II diabetes mellitus and to determine the relationship between capillaroscopic findings and clinical manifestations. Methods: Observational, descriptive and prospective of patients with diabetes mellitus II selected by inclusion and exclusion criteria. Subjects presenting signs/symptoms or history of any collagen disease, trauma presence in the nailfold due to cosmetic treatment or nail polish, were excluded. The capillaroscopy was performed by an experienced rheumatologist in a room with an ambient temperature of 20–23oC. The fourth and fifth fingers of the nondominant hand were chosen. The capillaries were observed using a 10x magnification capillaroscope (Dino-Lite) and photographs of the last distal row of capillaries were taken. The following capillaroscopic parameters were considered: capillary diameter (ectasia and giant capillaries), crosslinked capillaries, capillary tortuosity, ramified capillaries, avascular zones, hemorrhages, dominant morphology, subpapillar venous plexus visibility, cuticulitis and SD pattern. The images were analyzed by an experienced rheumatologist. Data was analyzed using SPSS. The non-parametric correlations were performed by tau_b Kendall and values were considered statistically significant when p>0.01 and they had two tails. Results: 65 patients were included in the study, with a mean age of 57 years [39–80], of which 75% [49] were women and 25% [16] men. The capillaroscopic findings were evident in 83% of the study population. The most frequent alterations were tortuous capillaries in 63% [41], cross-linked capillary in 59% [38], avascular areas in 48% [34], ectasias in 31% [25]. In smaller frequency, giant capillaries 14% [9], arborified capillaries 11% [7], no haemorrhages, no SD pattern. The capillaroscopic findings representing vascular damage were greater in patients with Diabetes Mellitus than in the control group (Figure 1 ). Moreover, the capillary morphology in the control group was open versus tortuous in patients with DM. Those patients with capillaroscopic alterations had a longer time of evolution of the disease with an average of 12.8 years, compared to those who did not present alterations that had a mean evolution of the disease of 8.5 years, which shows that those capillaroscopic alterations represent progressive endothelial damage. In addition, an association between the presence of retinopathy and capillary damage at the nail bed level was demonstrated (p>0.001). Conclusions: Capillaroscopy has proven to be a non-invasive, reproducible and reliable technique for the evaluation of vascular microarchitecture within a large group of rheumatic diseases of the scleroderma spectrum. However, it has been shown that it can be used for evaluation other diseases outside the field of Rheumatology such as diabetes, being a tool that should be known by primary care physicians and healthcare workers. Disclosure of Interest: None declared